How community therapists describe adapting evidence-based practices in sessions for youth: Augmenting to improve fit and reach - Kim, Joanna J. (J Community Psychol, 2020)
AIMS: The study sought to 1) characterize the types and frequency of session-level adaptations made to multiple evidence-based practices (EBPs) and 2) identify therapist-, client- and session-level predictors of adaptations. METHOD: Within the community implementation of multiple EBPs, 103 community mental health therapists reported on 731 therapy sessions for 280 clients. Therapists indicated whether they adapted EBPs in specific sessions and described adaptations in open-ended responses. Responses were coded using the Augmenting and Reducing adaptations framework. Multilevel logistic regression analyses examined predictors of Augmenting and Reducing adaptations. RESULTS: Therapists reported making adaptations in 59% of sessions. Augmenting adaptations were reported more frequently than Reducing adaptations. Multilevel models showed that greater therapist openness to EBPs, younger child age, and presenting problems were associated with Augmenting adaptations. Child presenting problem of externalizing problems predicted fewer Reducing adaptations compared to internalizing problems. CONCLUSION: This study extends the growing research examining adaptations within the context of system-driven implementation of multiple EBPs by applying the Augmenting and Reducing adaptation framework to the session-level.